Mechanistic insights and multiple characterizations of cadmium binding to animal-derived biochar. (March 2020) - Lei, Sicong; Zhu, Ling; Xue, Cong; Hong, Chengyi; Wang, Junliang; Che, Lei; Hu, Yongfeng; Qiu, Yuping
Abstract: Cattle-derived biochar (CB), which is derived from industrial pyrolysis of cattle carcasses in harmless treatment plants, is a naturally occurring mineral form of carbonate-bearing hydroxyapatite (CHAP) with a small amount of elemental carbon. CB has 4.02% of carbonate content, which falls under the B-type substitution of CHAP. In this work, the Cd(II) sorption capacity of CB was determined to be 0.82 mmol/g, with 97.6% of the Cd(II) uptake contributing to CHAP and only 2.36% of the Cd(II) uptake contributing to the elemental carbon component. The calculation and linear combination fitting (LCF) of Cd L 3 -edge X-ray absorption near-edge structure (XANES) analysis indicated that the contributions of Cd(II) species to CB presented the following order: ion exchange (57.6%–61.0%) > precipitation (24.4%–29.9%) > surface complexation (12.5%–13.4%). The depth dependent X-ray photoelectron spectroscopy (XPS) showed the presence of ion exchange, which is accompanied by intraparticle diffusion. LCF of XANES and Rietveld analysis of X-ray diffraction (XRD) demonstrated that Cd(II) was precipitated in the form of Cd5 H2 (PO4 )4 ·4H2 O on the CB surface. Furthermore, the precipitate was directly observed and identified by scanning electron microscopy with energy-dispersive spectroscopy (SEM-EDS). Consequently, we revealed the intricate binding mechanism of Cd(II) to CHAP-rich CB and confirmed the importance of surface precipitation. Graphical abstract: Image 1 Highlights: The mineral component of cattle-derived biochar (CB) dominated Cd immobilization. The intricate binding mechanism of Cd to CB was quantitatively evaluated. Ion exchange played a significant role in the Cd immobilization of CB (57.6%–61.0%). Spectro-/micro-scopic methods confirmed the precipitate of Cd5 H2 (PO4 )4 (24.4–29.9%). Surface complexation with functional groups of CB was relatively weak (12.5%–13.4%). Abstract : The intricate binding mechanisms of cadmium to cattle-derived biochar were quantitatively evaluated by XANES, SEM-EDS and XPS.